Role of regional cooperation and integration in improving energy insecurity in South Asia - Tapan Sarker; Shanawez Hossain; K. M. Nazmul Islam (Asian Development Bank Institute (ADBI), 2020)
Energy security affects national security as well as the availability, extraction, and utilization of natural resources like water, agriculture land, and mining resources. Therefore, energy security is a nation's ability to meet the energy needs of its inhabitants uninterruptedly at an affordable price-both in the short and in the long term. Over the last two decades, the energy security landscape has changed enormously at the global, regional, and local levels. This is particularly true in the context of South Asia, which has experienced rapid economic growth. However, wide disparity exists in terms of its energy security across the regions and between and within countries in Asia. These interrelated aspects, coupled with natural resource and energy constraints, are critical for Asia's long-term growth and development. In particular, people see enhancing energy security through regional cooperation as an important precondition for improving its relationship to regional trade and cooperation. This paper critically examines the literature on energy security in Asia and identifies existing gaps. In particular, the paper provides a growth nexus overview of Asia in the face of a resource-constrained future and discusses key challenges and potentials in enhancing energy security in the region. This paper shows that increasing regional cooperation can help to improve the access to energy among the energy-deficit developing countries in Asia and can benefit the region in terms of the preservation of natural assets, agricultural production, and food security. The paper concludes that enhancing regional cooperation and integration in different layers of resource sharing, production, and trade can bring countries together into an interdependence network to ensure maximum use of renewable and non-renewable energy resources.
Keywords: F15; Q43; R11; 330; energy security; regional cooperation; regional integration; water-energy-growth nexus; South Asia